Empowering women entrepreneurs through digital marketing mentoring: A community service for GMIT Genesaret Women’s Group in Kupang City - Dominikus Kopong Toni Aman; Anggi Somba Poddala; Sonia Virgarini Nawi; Yonas Ferdinand Riwu (Nur Science Institute, 2026)
This Community Service Activity (CSA) aims to empower the GMIT Genesaret Women's Group in Kupang City through increasing entrepreneurial capacity and digital-based marketing. This program also encourages the use of local potential, especially the processing of papaya into value-added products. The methods used include counseling, practical training, discussions, and participatory mentoring. A total of 30 participants were actively involved in the entire series of activities. Evaluation is conducted through pre- and post-tests, as well as observations throughout the process. The results of the activity showed an increase in participants' understanding of entrepreneurship concepts, mastery of digital marketing instruments, and skills in processing papaya into creative snacks. Participants' enthusiasm and motivation to develop digitally based businesses also increased. Participants were able to understand the steps of starting an online business and use social media as a means of promotion. The implications of this activity emphasize the need for more intensive follow-up assistance, such as content creation training, product packaging, and business registration on digital platforms.